Effect of Wheat Bread Incorporated with Chamomile and Wild Thyme on Glycemic Response, Antioxidant Status and Inflammation in Type 2 Diabetic Individuals - Imran Khan; Imtiaz Ahmad; Jamil Ahmad; Mostafa I. Waly; Stuart K. Johnson (Natural Resources for Human Health, 2026)
Previous studies suggest that bread incorporated with chamomile and wild thyme powder exhibit lower starch digestibility and higher antioxidant activity in vitro and hence its intake may suppress postprandial blood glucose and enhance antioxidant status in humans. The present study determined the effect of bread incorporating chamomile and wild thyme on blood glucose, antioxidant status and inflammation in type 2 diabetic individuals. Sixteen male subjects consumed both control bread (CB) or bread incorporating 3 % chamomile and wild thyme powder in two separate sessions. Blood glucose was measured by finger-prick method at fasting and then postprandially for 2 h. Antioxidant and inflammatory markers were measured at fasting and 2 h after consumption. A non-significant decrease in blood glucose (-8.30 ± 2.39 mg/dl; p = 0.411) was observed after the consumption of chamomile and wild thyme-containing bread (CWB) compared to CB. Compared to baseline, the consumption of CWB non-significantly increased total polyphenols, total antioxidant capacity (TOAC) and superoxide dismutase (SOD) activity by 6.12%, 20.32% and 15.17%, respectively (p for all